Effect of oestradiol treatment on 5-HT and dopamine-mediated neuroendocrine responses. - Best, N; Rees, M; Barlow, D; Cowen, P (1992)
We assessed the effect of oestradiol treatment in women on the endocrine responses to the 5-hydroxytryptamine (5-HT) precursor, L-tryptophan (LTP) (5 g i.v.) and the dopamine agonist, apomorphine (0.005 mg/kg s.c.). Following oestradiol implant (100 mg s.c.) the prolactin (PRL) response to LTP was significantly enhanced but there was no change in the growth hormone (GH) response to apomorphine. There was, however, a significant correlation between post-implant oestradiol concentrations and post-implant apomorphine-induced GH release. The results indicate that oestrogen treatment may facilitate 5-HT-mediated PRL release and could also influence the regulation of dopamine-mediated GH responses. However, further studies are needed to exclude direct effects of oestradiol on the pituitary release of PRL and GH.